L’Apocolocyntosis come Opera Storica - Ramelli, Ilaria (Gerión. Revista de Historia Antigua, 2001)
The work first focuses the attention on the historical sources that deal with the Apocolocyntosis (Juvenal and Cassius Dio in particular) and tries to show the significance of the irony of this enigmatic title. Then the second part presents an analysis of several passages of the Apocolocyntosis and their parallels in some historical authors of the second and third centuries.